The deconfiguration of the Continuous Cash Benefit (BPC) under ultra neoliberalism - Peres, Viviane Aparecida Pereira (Argumentum, 2024)
This article aims to analyze the changes in the Continuous Provision Benefit - BPC, mainly the regulated eligibility criteria in the context of the advent of the neoliberal project in Brazil and its constant subsequent changes. In the Temer and Bolsonaro governments, a scenario of fiscal austerity and the materialization of Social Security counter-reforms, several changes were made through infra-constitutional normative acts that profoundly restricted access to the benefit. In this sense, analyzing changes in the BPC, especially in ultraneoliberal governments, is essential to demonstrate the setbacks in access to the rights of people with disabilities and the elderly and to contribute to collective struggles for the suppression of such measures.